1966
DOI: 10.1111/j.2042-7158.1966.tb07906.x
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour transmission properties of free polymer films

Abstract: The water vapour transmission properties of selected hydrophilic, lipophilic, and mixed hydrophilic‐lipophilic polymer systems, cast as free films, have been examined as a function of time, film thickness, plasticiser concentration, and film formulation. An inverse linear relationship was established between the logarithm of the water vapour transmission rate (Rwvt) and the logarithm of film thickness in the presence of the various plasticiser concentrations for the three systems studied. The lipophilic n‐buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…Increasing the concentration of plasticizer in the film caused first a decrease, and then an increase in water vapor permeation. Banker et al (36) obtained similar results with films of hydroxypropyl cellulose and poly(buty1 methacrylate). It was postulated by Lachman and Drubulis that plasticizer fills the interstices of the polymer, reducing permeation.…”
Section: Resultssupporting
confidence: 70%
“…Increasing the concentration of plasticizer in the film caused first a decrease, and then an increase in water vapor permeation. Banker et al (36) obtained similar results with films of hydroxypropyl cellulose and poly(buty1 methacrylate). It was postulated by Lachman and Drubulis that plasticizer fills the interstices of the polymer, reducing permeation.…”
Section: Resultssupporting
confidence: 70%
“…Banker, Gore, and Swarbrick (1966) reported a similar slight decrease in the water transfer rate or flux, but an increase in WVP values, with increasing thickness of hydroxycellulose films (range 40-260 mm). McHugh et al (1993) and Gennadios, Weller, Cole, and Gooding (1994) tried to explain the effect of the thickness on the permeability of hydrophilic films by introducing a modification to the calculation of the WVP.…”
Section: Water Vapour Permeabilitymentioning
confidence: 76%
“…Various hypotheses have been proposed to explain the increase in WVP with increasing film thickness. Barrer (1951) and Banker, Gore, and Swarbrick (1966) attributed the thickness effect to film swelling as a result of water-film interaction. Recently, other Authors McHugh et al, 1993) observed that as film thickness increased, the film offered enhanced resistance to water vapor transfer across it.…”
Section: Effect Of Thicknessmentioning
confidence: 96%